Toward to Combination of GIS-HBIM Models for Multiscale Representation and Management of Historic Center - Massimiliano Pepe; Donato Palumbo; Ahmed Kamal Hamed Dewedar; Enrico Spacone (Heritage)
The aim of this work is to identify a suitable methodology capable of integrating multiscale spatial information about an historic center drawn from a Geographic Information System (GIS) and Historical Building Information Modeling (HBIM). The method is based on a multiscale development system that can efficiently handle different types of geospatial information by exploring geomatic techniques and software for semantic and parametric modeling. Our case study of the historic center of Popoli (Italy) shows the quality of the proposed model and HGIS-BIM integration for building geometric models rich in semantic and parametric information, taking into account development at different levels of detail.